Free Soil, Free Labor, Free Men : the Ideology of the Republican Party before the Civil War With a New Introductory Essay. - Foner, Eric (Oxford University Press, USA, 1995)
Since its publication twenty-five years ago, Free Soil, Free Labor, Free Men has been recognized as a classic, an indispensable contribution to our understanding of the causes of the American Civil War. A key work in establishing political ideology as a major concern of modern American historians, it remains the only full-scale evaluation of the ideas of the early Republican party. Now with a new introduction, Eric Foner puts his argument into the context of contemporary scholarship, reassessing the concept of free labor in the light of the last twenty-five years of writing on such issues as w.